Födosöksbeteende och aktivitet hos brunbjörn (Ursus arctos) vid användning av två olika utfodringsmetoder - Vinnerheim, Ellen (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
The brown bear (Ursus arctos) is an omnivore that spends a lot of its time foraging in the wild. In zoos, the brown bear's foraging behaviour and activity level is depending on the management. To stimulate the brown bears to express their natural behaviours the zookeepers can feed the bears in a way that makes the bears forage for a long time. In this study, two different feeding methods were used to investigate if the brown bears at Borås Zoo would forage more and be more active during one of the feeding methods. The two different methods were chopped food and whole food and the food from both treatments was scattered in the bears' enclosure. The chopped food was also scattered in more places around the enclosure because there were more pieces of food. Five bears were observed for ten days, six times per day both before, during and between two feedings. The results show a difference between chopped food and whole food and the bears were more active and expressed more foraging behaviours when they were fed with chopped food. The first feeding was breakfast for the bears and the second was lunch, the bears expressed more foraging behaviours and were more active during breakfast when they were fed with chopped food. But during lunch when they got chopped food, they were more active but did fewer foraging behaviours compared with whole food. The bears' activity was low during the observations between the feedings, both during days with chopped and whole food. A further study is therefore recommended to find a feeding method that is activating the bears for a longer period. The result did also show individual differences in the behaviours between the bears, where the juveniles were more active than the adults and they expressed more play behaviour. With help of this study the feeding strategy for the bears in Borås Zoo can be improved which is important for the bears welfare and the zoo’s work with species conservation.